1991
DOI: 10.3109/14017439109098098
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinoscopy as an Emergency Diagnostic Procedure in Superior Vena Cava Syndrome

Abstract: Seven men and one woman (aged 20-70 years) with superior vena cava syndrome underwent diagnostic mediastinoscopy to elucidate the cause, which other, lesser procedures had not identified. Intraoperative frozen-section studies of the biopsy specimens revealed small-cell carcinoma (4 cases), large-cell carcinoma (1), squamous-cell carcinoma (1), large-cell lymphoma (1) and Hodgkin's lymphoma (1). Radiotherapy or chemotherapy was initiated within the following 24 hours in six cases. One of the tumors intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Kirschner [34] performed mediastinoscopy in 16 patients with SVCS without complication. Callejas et al [35] reported one wound infection and one carotid artery injury in eight such cases. Little et al [36] had no complications in eight patients who underwent cervical mediastinoscopy.…”
Section: Treatmentmentioning
confidence: 98%
“…Kirschner [34] performed mediastinoscopy in 16 patients with SVCS without complication. Callejas et al [35] reported one wound infection and one carotid artery injury in eight such cases. Little et al [36] had no complications in eight patients who underwent cervical mediastinoscopy.…”
Section: Treatmentmentioning
confidence: 98%
“…Tanı koyma başarısı %90 ve %100'lere ulaşır (12,13). Kanama ve enfeksiyon gibi risk oranı %0-7'dir (14,15). h) Endobronşiyal Ultrasonografik Biyopsi (EBUS) VKSS'lu hastalarda EBUS kullanımı ile ilgili bir bilgi şu an için yoktur.…”
Section: G) Mediastinoskopiunclassified
“…Operative endoscopy has gained a new significance in the evaluation of SVCS since echography has been introduced but the best diagnostic result is still obtained by the mediastinoscopy. Venous hypertension may increase the procedure-related risk [23][24][25][26][27].…”
Section: Diagnosismentioning
confidence: 99%